ANALISIS KESTABILAN PENGONTROLAN DUA POSISI PADA TANGKI BERINTERAKSI MENGGUNAKAN METODE DESCRIBING FUNCTION - Purwandito Tulus Asmoro (LPPM Politeknik Enjinering Indorama, 2019)
A water storage unit consisting of 3 interacted tanks, the operation will experience problems if using manual control, because if manual control is not optimal, then when filling the water in the three tanks will cause water overflow which results in a lot of wasted water. Two- position control or